Partisipasi Publik dalam Pembentukan Undang-Undang: Perspektif Perbandingan 5 (Lima) Negara Demokratis: Partisipasi Publik dalam Pembentukan Undang-Undang: Perspektif Perbandingan 5 (Lima) Negara Demokratis - Fahmi Ramadhan Firdaus (Jurnal Konstitusi, 2024)
Public participation is the heart of the legislative process. Participation is crucial to ensure that the laws produced genuinely reflect the needs and aspirations of society, as well as to embody democracy and strengthen legitimacy. Through a normative juridical approach, the research aims to compare public participation in law-making in five democratic countries, namely Indonesia, the United States, the Philippines, South Africa, and South Korea, by analyzing their Constitutions and laws and regulations. The findings can then be used as best practices that can be adopted by Indonesia. The results of the study show that the Constitutions of the United States, the Philippines, South Africa, and South Korea guarantee public participation in the legislative process. In contrast, the Indonesian Constitution only affirms People’s Sovereignty. However, normatively, Indonesia regulates the role of the public more comprehensively and technically in the law-making process at every stage, further reinforced by the Constitutional Court Decision No. 91/PUU-XVIII/2020, which mandates that the role of the public be more meaningful in law-making, as participation is a constitutional right held by citizens.